Effect of Limb Position on Measurements of the Quadriceps Muscle Length/Femoral Length Ratio in Normal Beagle Dogs - Murakami, Sawako; Nagahiro, Yukari; Shimada, Masakazu; Kanno, Nobuo; Suzuki, Shuji; Yogo, Takuya; Harada, Yasuji; Hara, Yasushi (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objectives Dogs with patella alta reportedly have a shorter extensor mechanism than normal dogs. The present study aimed to measure the length of the extensor mechanism and to assess the effect of limb position on the quadriceps muscle length (QML)/femoral bone length (FL) ratio.Study Design Three-dimensional computed tomography images were taken of 12 Beagle dogs. Each dog underwent computed tomographic imaging 24 times with different limb positions. The QML/FL was measured on each image, along with the hip flexion–extension, hip abduction–adduction and stifle flexion–extension angles. Multiple regression analysis was used to determine the effect of these angles on the QML/FL.Results The QML/FL was increased with the hip extended (standardized partial regression coefficient 0.855 with linear plotting, 0.829 with log plotting) and with the stifle flexed (standardized partial regression coefficient 0.814 with linear plotting, 0.800 with log plotting). The partial regression coefficient of the hip abduction–adduction angle was small, indicating a small impact on the QML/FL. The 95% confidence range of the QML/FL with the hip extended and stifle flexed was 0.87 to 1.00 (mean ± standard deviation: 0.93 ± 0.03).Conclusion The QML/FL was more influenced by joint angles when the hip was flexed or the stifle was extended. Hence, these positions should be avoided when evaluating the QML/FL so that the QML is less altered by slight positioning disparities.
Keywords: quadriceps muscle length; patellar luxation; patella alta; QML/FL; dog